Evolutionary psychology and economic theory - Koppl, Roger, 1957- (Amsterdam ; Oxford : Elsevier JAI, 2004)
The contributors to this volume seriously engage issues in the crossroads where biology, psychology, and economics meet. The volume makes several important contributions to the area and provides an overview of the current state of knowledge. Eleven papers expose opportunities and challenges for Austrian economists with regard to developments in the field of evolutionary psychology.
Includes bibliographical references.
oif 13/02/15
Loan
Keywords: Austrian school of economics; Evolutionary economics; Group selection (Evolution).; Evolutionary psychology